Topical collection on football research - Billingham, J.; Dunn, M. (Sports Engineering, 2023)
The symbiotic relationship between football, industry, and academia is deepening, creating opportunities to develop every facet of the game. The combination of new technology, research-led approaches, and football expertise is cultivating an environment where ideas can be developed, assessed, and implemented faster than ever. It is important to ensure that the implementation of these ideas benefit the world of football and are supported by evidence.